The Internet Soapbox Perspectives on a Changing Public Sphere - Terje Rasmussen (Scandinavian University Press (Universitetsforlaget), 2016)
This book reviews Internet research and political theory seeking theoretically "cool-headed" perspectives on the current public political spaces in advanced societies. Aspects of the political theories of Rawls and Habermas are discussed and contrasted with contestation-oriented theories. In light of how the Internet takes part in structurally transforming the public sphere, the book draws on sociological and realist insights in order to encircle a more realist view. It briefly reconsiders such strange bedfellows as sociological systems theory (Niklas Luhmann) and political realism (eg. Bernard Williams). The purpose is not to construct a realist theory of the internet-based public sphere, but to point out central insights on which such a theory can be built.